Analisis Pemanfaatan Data Sensus Harian dalam Pelaporan Indikator Pelayanan Rawat Inap di RSUD Syekh Yusuf Gowa - Ahmad Jayadie; Ruslan Agussalim; Syamsuddin S; Muh. Erwin Rosyadi (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Background, Reporting of inpatient service indicators plays an important role in evaluating hospital performance. This study analyzes the use of daily inpatient census data in compiling reports of inpatient service indicators for the first quarter of 2023 at Syekh Yusuf Hospital, Gowa Regency. The data used includes the daily inpatient census for the period January–March 2023 using the total sampling method. The indicators calculated include Bed Occupancy Rate (BOR), Average Length of Stay (AvLOS), Turn Over Interval (TOI), Bed Turn Over (BTO), Net Death Rate (NDR), and Gross Death Rate (GDR). The results of the study show that the calculation of indicators only uses data on days of treatment and length of stay of patients as the basis for analysis. Reporting is done manually and computerized in the form of tables, bar graphs, and Barber Johnson graphs. However, data utilization has not been optimal because the results obtained are not entirely accurate. In conclusion, the implementation of processing and processing of daily inpatient census data needs to be improved in order to produce more valid and accurate reports”.